LOCAL COMMUNTIES ATTITUDES AND PERCEPTIONS TOWARDS COMMUNITY BASED TOURISM IN IKO-ESAI COMMUNITY, CROSS RIVER STATE, SOUTH EAST, NIGERIA - A. A., Nchor; C. O., Agbor (International Journal of Research -GRANTHAALAYAH, 2018)
The role of local communities’ attitudes and perceptions in the determination of tourism development in host destination are critical and cannot be overemphasized. The study sought to determine the perceptions of local residents towards tourism development in Iko-Esai Community of Cross River State, Nigeria. Questionnaires and interviews were used to collect primary data while secondary data was sourced from documents in CERCOPAN Office, journals, as well as past studies in the area. A total of one hundred and forty-six (146) questionnaires were administered to respondents in two (2) selected wards in the community. Data was analyzed using frequencies and percentages. Results showed overwhelming agreement by respondents that the community is fully involved in all the activities of tourism development in the area including benefit sharing, decision making, as well as the overall management of tourism. 54.11% of respondents agreed that ecotourism has contributed positively to poverty alleviation while 57.54% of the respondents sampled were of the opinion that profit form ecotourism is distributed directly or indirectly to indigenes. Ecotourism has successfully enhanced cooperation between the local communities and external bodies as reflected in the position of 97.94% of the respondents. The respondents were of the views that CERCOPAN – an NGO operating a primate rehabilitation project in the community has been working closely with them to save the primates in the area from further population depletion. On benefit sharing, 91.78% of the respondents sampled agreed that the community participated in sharing economic benefits from ecotourism while 67% of the respondents were of the opinion that length of residency in the community affects people’s attitudes and perceptions towards tourism development. Though there was a report of human-wildlife conflicts in the area, a greater percentage of the respondents (69.87%) were of the opinion that the conflicts were not a problem in the community as the challenge was averted because of the fencing of the area by CERCOPAN. CERCOPAN should encourage the community to step up their support for tourism development in the area through increased benefit sharing and the development of some basic infrastructures like health centers and water projects in the community.